The same human complement factor B allele of major histocompatibility complex (MHC) class III allele is conserved in chimpanzee and gorilla, stressing its immune importance - Antonio Arnaiz-Villena; Christian Vaquero-Yuste; Ignacio Juarez; José Manuel Martín-Villa; Fabio Suarez-Trujillo (Academia Molecular Biology and Genomics)
The association between HLA (human major histocompatibility complex, MHC) and diseaseshas been searched for more than 40 years. Mechanisms of association and pathogenesis of this linkage are still unknown. We have put forward that complement alleles should be studied together with all other MHC genes. Complement genes (MHC class III) are located in the same chromosome as classical and non-classical class I and II MHC genes from birds to humans for million years and are usually also linked to diseases. It is necessary to study complotypes (alleles of C2, Bf and C4) and extended MHC (or HLA) haplotypes together in order to elucidate the association between HLA/MHC and diseases sound pathogenesis. Certain complement alleles, like the one previously described by the authors (Patr-Bf*A01), are maintained after one speciation process in apes, i.e., to chimpanzee and humans. It is described in the present paper that the same allele is also found in Gorilla gorilla (Gogo-Bf*A01, rs641153). Bf proteins are fundamental in the fight against microbes by means of the so-called complement alternative pathway. The evolutionary forces that maintain this allele invariant through two speciation processes (gorilla, chimpanzee and man during about 10 million years at least) are still unknown but it suggests that this Bf allele has a great importance for self-maintenance and microbial defense. In addition, nature has kept complement genes in a short chromosome stretch, the MHC, in species ranging from birds to human during the last 300 million years, suggesting that class I, II and III genes work together in maintaining individuals’ self-defense and avoiding diseases.